Perioperative and long-term functional outcomes of robot-assisted versus open partial nephrectomy: A single-center retrospective study of a Japanese cohort. (March 2022) - Takahara, Kiyoshi; Fukaya, Kosuke; Nukaya, Takuhisa; Takenaka, Masashi; Zennami, Kenji; Ichino, Manabu; Sasaki, Hitomi; Sumitomo, Makoto; Shiroki, Ryoichi
Abstract: Objective: This study aimed to compare the perioperative and long-term functional outcomes between robot-assisted partial nephrectomy (RAPN) and open partial nephrectomy (OPN) in Japanese patients. Methods: We retrospectively analyzed 242 patients who underwent either RAPN or OPN between 2007 and 2017 at our hospital. Propensity score matching was carried out between the two groups at a ratio of 1:1. Perioperative outcomes and postoperative estimated glomerular filtration rates (eGFR) were compared at one and three years of follow-up. Results: After propensity score matching, we evaluated 39 patients from each group. The ischemia duration of the RAPN group was significantly shorter than that of the OPN group (18 vs. 24, p  < 0.001). Moreover, the estimated blood loss (EBL) was significantly lower in the RAPN group than in the OPN group (50 vs. 174, p  < 0.001). However, there were no significant differences in the postoperative eGFR between the two groups at one or three years of follow-up (OPN 54.8 vs. RAPN 61.2, p  = 0.109, and OPN 54.8 vs. RAPN 55.5, p  = 0.262, respectively). Conclusion: RAPN resulted in shorter ischemia durations and lower rates of EBL than did OPN; however, no differences in long-term renal function were observed between RAPN and OPN in our propensity-score matched Japanese cohort. Highlights: This study aimed to compare the perioperative and long-term functional outcomes of RAPN and OPN in Japanese patients. RAPN resulted in shorter ischemia durations and lower rates of estimated blood loss than OPN. No differences in long-term renal function were observed between RAPN and OPN.